Effects of Visual and Text-Based Forum Graphical Interfaces on Participants Situation Awareness - Leiva-Lobos, E; Ponce-Arias, H (Institute of Electrical and Electronics Engineers Inc., 2019)
The present study experimentally tested whether participating in dialogues using a visual-based forum application increases participants situation awareness compared with using a text-based forum. The text-based forum used in the study was a well-known open-source application called Discourse meanwhile the visual-based forum was an application specially developed for this study that we called VisualMail. This tool was designed based on a theory of dialogue and included functionalities to visualize the threads of the argumentation. A total of 42 participants interacted with the two applications in a withinsubject design. Situation awareness was assessed with an instrument called SAGAT (Situation Awareness Global Assessment Technique) that measures perception of the environment, comprehension of the present situation and projection of future states and events. The experimental results indicate that participating in dialogues using VisualMail significantly increases situation awareness on its three dimensions, with large effect sizes observed in each of them: perception (d = 1.02), comprehension (d = 1.64) and projection (d = 1.38). © 2019 IEEE.